The construction of gender-responsive classrooms in a higher education institution: An exploration of teachers’ situated knowledge, pedagogical practices, and common challenges in promoting gender equality - Bastida Jr., Ernesto L.; Abargos, Jerbert A.; De Lara, Rudy Bhonne R.; Saysi, Jhonies G.; Geronimo, Jet Martine S.; Kim, Rhea A.; Luching, Ma. Eunice S.; Añonuevo, Bien M. (Indonesian Journal of Social Sciences, 2025)
Gender equality is one of the foundations of inclusive learning environments, as emphasized in the Sustainable Development Goals (SDGs). In higher education, the institutionalization of Gender and Development (GAD) programs was initiated to contribute to the attainment of SDG 5. Using grounded theory research design, 20 higher education teachers’ situated knowledge, pedagogical practices, and common challenges in mainstreaming gender equality in classrooms were explored. Data were collected through semi-structured interviews and focus group discussions. Results indicated that while most teachers were well aware of various gender-related issues, policies, and statutory laws, some of them were not able to mobilize effective practices that strengthen gender equality. Common challenges in GAD mobilization were a lack of an integration framework and GAD specialists, a contextualized plan, cultural differences, low prioritization, coordination gaps, a lack of comprehensive knowledge about gender equality, and inappropriate implementation approaches. Drawn from the participants’ responses, the researchers generated a theory labeled as “Praxis-Oriented Construction of Gender-Responsive Classrooms,” which revealed how gender equality was understood, practiced, and challenged in higher education. The researchers conclude that gender equality has not yet been successfully mainstreamed in higher education; it still needs to have clear and well-supervised integration policies to make higher education classrooms genuinely gender-responsive.